Analisis Tingkat Kepuasan Pengunjung Terhadap Harga, Layanan, Dan Fasilitas Usaha Kopi Di Koup Galaxy - Ahmad Faqih Syukri; Tiara Putri Fadyanto; Dewi Sri Woelandari (International Forum of Researchers and Lecturers, 2024)
This research aims to analyze the level of visitor satisfaction with prices, services and coffee business facilities in Koup Galaxy. This research is quantitative research. The population selected in this research is Koup Galaxy consumers who have visited. The sample collection technique chosen was nonprobability sampling with a purposive sampling method. The data source in this research was obtained from distributing questionnaires to 100 respondents. The analytical tool used to assist this research is the structural equitation model (SEM) - SmartPLS 3.0. Furthermore, the results given in this research are (1) Price has a positive and significant influence on the level of visitor satisfaction at Koup Galaxy. (2) Service quality has no influence on the level of visitor satisfaction at Koup Galaxy. (3) Facilities have a positive and significant influence on the level of visitor satisfaction at Koup Galaxy.